A aplicabilidade da cláusula democrática do Mercosul: o caso de suspensão do Paraguai - Paiva, Ana Cláudia Alves Cunha (2020)
The MERCOSUR Democratic Clause is a fundamental norm of the bloc, first provided in the Ushuaia Protocol, signed in 1998. The basis of the clause derives from the premise that the full functioning of democratic institutions is a prerequisite for the entrance and permanence in the bloc. The present research intends to analyze the applicability of this clause through the analysis of the first concrete case in which it was invoked. The case occurred in 2012, when, during the XLIII Summit of Heads of State of MERCOSUR, it was decided to suspend Paraguay after the member states concluded that the impeachment process of Paraguayan President, Fernando Lugo, have not followed democratic principles. Concurrent with the application of the penalty to the country, the other member countries approved Venezuela's effective accession to MERCOSUR. Since the event raised some questions and controversies, this research intends to identify and analyze some of the variables that may have impacted on the decision-making process that culminated in the decision to suspend Paraguay. The analysis to be carried out has as a background the theoretical debate about the new regionalism and integration processes. The research will be built from bibliographic and documentary research, as well as reading of the norms related to the object.